2020
DOI: 10.1186/s13068-020-01820-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics-based identification and characterization of a superior 2,3-butanediol dehydrogenase for Zymomonas mobilis expression

Abstract: Background Zymomonas mobilis has recently been shown to be capable of producing the valuable platform biochemical, 2,3-butanediol (2,3-BDO). Despite this capability, the production of high titers of 2,3-BDO is restricted by several physiological parameters. One such bottleneck involves the conversion of acetoin to 2,3-BDO, a step catalyzed by 2,3-butanediol dehydrogenase (Bdh). Several Bdh enzymes have been successfully expressed in Z. mobilis, although a highly active enzyme is yet to be ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The effects of different temperature and pH value on (2R, 3R)-BDH and (2S, 3S)-BDH activity were investigated by using 50 mM 1,2-BD mixture and 0.3 mM NAD + as substrate and coenzyme, respectively. The influence of the buffer pH (6-12) were investigated at room temperature using 50 mM potassium phosphate buffers (pH 6-8), glycine-NaOH buffers (pH 9-10), and Na2HPO4-NaOH buffers (pH [11][12]. The results indicated that the activities of two enzymes were obviously increased with the increase of pH values (Figure 1AB).…”
Section: Enzymatic Properties Of (2r 3r)-bdh and (2s 3s)-bdh For 12-bd Mixturementioning
confidence: 97%
See 2 more Smart Citations
“…The effects of different temperature and pH value on (2R, 3R)-BDH and (2S, 3S)-BDH activity were investigated by using 50 mM 1,2-BD mixture and 0.3 mM NAD + as substrate and coenzyme, respectively. The influence of the buffer pH (6-12) were investigated at room temperature using 50 mM potassium phosphate buffers (pH 6-8), glycine-NaOH buffers (pH 9-10), and Na2HPO4-NaOH buffers (pH [11][12]. The results indicated that the activities of two enzymes were obviously increased with the increase of pH values (Figure 1AB).…”
Section: Enzymatic Properties Of (2r 3r)-bdh and (2s 3s)-bdh For 12-bd Mixturementioning
confidence: 97%
“…Previous studies showed that diol dehydrogenases such as 2,3-butanediol dehydrogenase (BDH) could efficiently catalyze the interconversion of 2,3-BD and AC [8][9][10][11][12]. Substrate specificity assays indicated that the BDH enzyme could oxidate 1,2-pentadiol and 1,2-propanediol into the corresponding secondary ketone in the presence of NAD + , suggesting the BDH enzyme might have potential for the conversion of 1,2-BD to HB [13,14].…”
Section: Screening Of Enzymes For Hb Production From 12-bdmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than ethanol, Z. mobilis possesses endogenous abilities to produce other fuel alcohols, such as isobutanol and 2, 3-butanediol. For the 2, 3-butanediol production, recombinant strains were successfully developed by expression of acetolactate synthase, acetolactate decarboxylase, and butanediol dehydrogenase encoding genes [ 96 , 97 ]. The best-enhanced strain was able to produce more than 10 g/l of 2, 3-butanediol from glucose and xylose as well as sugar streams derived from deacetylation and mechanical refining [ 96 ].…”
Section: Recent Metabolic Advances In Microorganism For Biofuel Produ...mentioning
confidence: 99%
“… 3 Second, it has only a low tolerance toward inhibitory substances, arising, for example, from treatment of lignocellulosic biomass. 4 Lastly, despite some recent developments to expand the extraordinary capacity for ethanol synthesis toward other products such as lactate, 5 isobutanol, 5 , 6 poly-3-hydroxybutyrate, 7 and 2,3-butanediol, 8 there is an increasing need for efficient genetic tools for metabolic engineering.…”
Section: Introductionmentioning
confidence: 99%